Generating temperature cycle profiles of different solar photovoltaic module technologies from in-situ conditions for accurate prediction of thermomechanical degradation - Bebeto Nii Sampa Sampah; Frank K. A. Nyarko; Benjamin Atribawuni Asaaga; Jefferson Aggor (International Journal of Energetica)
The IEC61215 TC200 is a rigorous approval thermal cycling test process that assesses the reliability of solar photovoltaic modules and offers a 25-year lifetime guarantee. However, previous research has shown that installed solar photovoltaic modules experience different rates of degradation depending on the location and climate with most research focused on crystalline silicon. In this study, outdoor weathering data obtained from a rig set up in Kumasi, Ghana for the year 2014, is used to generate thermal cycles for 5 different technologies including monocrystalline, polycrystalline, and amorphous silicon, Copper Indium Gallium Selenide (CIGS) and Heterojunction-With-Intrinsic-Thin-Layer (HIT). From the results, the highest yearly average of the maximum and minimum temperatures, and ramp rates of 54.8oC, 26.1oC, and 6.05oC/h respectively are recorded in CIGS. Polycrystalline recorded the least temperatures of 45.2°C and 23.9°C while HIT recorded the least ramp rate of 4.45°C /h. A comparison between the 2014 and the IEC61215 thermal cycles show extremely wide differences which could explain the higher degradation rates and shorter life of installed solar photovoltaic modules. The procedure adopted in this research can be repeated at different locations to obtain technology-specific thermal cycling profiles to evaluate the thermomechanical damage and predict the life of different solar photovoltaic modules.